2022
DOI: 10.3390/v14122614
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Cocktails in the Post-COVID Rehabilitation

Abstract: Increasing evidence suggests that gut dysbiosis is associated with coronavirus disease 2019 (COVID-19) infection and may persist long after disease resolution. The excessive use of antimicrobials in patients with COVID-19 can lead to additional destruction of the microbiota, as well as to the growth and spread of antimicrobial resistance. The problem of bacterial resistance to antibiotics encourages the search for alternative methods of limiting bacterial growth and restoring the normal balance of the microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This may be due to a reduction in the intensity of the inflammatory response due to a decrease in bacterial load. In conducted studies, a decrease in CRP levels during bacteriophage administration was also noted [16,22].…”
Section: Discussionmentioning
confidence: 90%
“…This may be due to a reduction in the intensity of the inflammatory response due to a decrease in bacterial load. In conducted studies, a decrease in CRP levels during bacteriophage administration was also noted [16,22].…”
Section: Discussionmentioning
confidence: 90%
“…The titers obtained by growing the phages in liquid nutrient medium showed that they could effectively inhibit the growth of K. pneumoniae culture and indicated sufficient virus productivity to obtain high concentrations in the final preparation. A real-time in vitro phage lysis assay showed that the selected phage cocktail could effectively lyse Kl 315 planktonic cells of K. pneumoniae culture and disrupt small microcolonies adhered on the glass surface 19 . Therefore, the cocktail of bacteriophages vB_KpnS_FZ10, vB_KpnP_FZ12 and vB_KpnM_FZ14 was chosen for further studies on more mature biofilms carried out in the present work and vB_KpnP_FZ12 was selected as the most productive on Kl 315 strain to compare the efficacy of a single phage vs three-phage cocktail on K. pneumoniae biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…The selected bacteriophages were tested in vivo as a part of a broader phage cocktails in published studies 18 , 19 . Real-time in vitro analysis of K.pneumoniae (Kl 315) culture lysis with a cocktail of selected phages was carried out in a previous study using imaging with a 3D Cell Explorer microscope 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous superficially plausible hypotheses may be formulated to seek unification across the many different vulnerability markers, but diet and social geography (in particular as it relates to diet and exposure to pollution and pathogens) have documented effects on host microbiome profiles, which, in turn, have attracted growing attention as possible influences on COVID-19 vulnerabilities [50,52,[160][161][162]165,170,173,183,[190][191][192][193]200,217]. Reasonable interpretations for how such microbe-virus interplay may arise must recognize not only the observations that bacteria use proteases to modulate host physiology in ways that benefit bacterial persistence and replication [171,[237][238][239] and inter-bacterial competition [239][240][241] but also the evidence that bacterial proteolytic action can tangibly modulate viral efficacy [172].…”
Section: Future Directionsmentioning
confidence: 99%
“…While substantial research has been devoted to co-pathology among various microbes and the SARS-CoV-2 virus [48][49][50][51][52], this hypothesis aims to assess knowledge of the symbiotic host-protective capacity of some bacteria [50,53] while focusing on putative mechanisms at molecular levels of detail, with potential application to therapeutic development. In particular, a novel hypothesis is rationalized, tying key aspects of host protection to the relative capacity of different bacterial serine proteases to interact with the SARS-CoV-2 Spike protein (and other comparable viral Class I fusion proteins present in various other coronaviruses and retroviruses) in a manner that may interfere with the pathological TMPRSS2-mediated process of Spike cleavage and host-membrane permeation.…”
Section: Introductionmentioning
confidence: 99%